Strategies applied to modify structured and smooth surfaces: A step closer to reduce bacterial adhesion and biofilm formation - Uneputty, A.; Dávila-Lezama, A.; Garibo, D.; Oknianska, A.; Bogdanchikova, N.; Hernández-Sánchez, J.F.; Susarrey-Arce, A. (Colloid and interface science communications, 2022)
Nearly a century has passed since the discovery of the first antibiotics. With each passing decade, more bacterial strains developed resistance towards existing antibiotics. Alternative methods to reduce contamination by bacteria and biofilms have arisen to reduce the pressure on existing or currently developed antibiotics. This review highlights promising approaches to prevent bacterial contamination of the surface. Special attention is paid to antibiotic-free antibacterial strategies that are not affected by bacterial resistance. The approaches have been divided into four categories: (i) anti-adhesive, (ii) contact active, and (iii) biocide attached/biocide release, which can be integrated with (iv) topographical modification. Anti-adhesive approaches can reduce the adhesion between bacteria and a solid surface to prevent bacteria from contacting and contaminating the surface. Contact active approaches provide antibacterial activity by attachment of antibacterial agents to the substratum. Biocide attached/biocide release integrates contact-release of toxic chemicals to bacteria attached to the surface. Lastly, topographical modification relies on approaches to produce small structural features capable of matching cellular components killing bacteria. Combining one or more antibacterial strategies can lead to a more robust approach to deal with dangerous pathogenic bacterial species. In this case, a way forward is by combining various coatings onto topographically modified surfaces, enabling multifunctionality to reduce adhesion and biofilm formation. A perspective on the current antibacterial surface challenge is provided. [Display omitted] •Chemical strategies, such as anti-adhesion, contact active, and biocide attachment/release increase surface functionality•Substrates with micrometric or nanometric features made using physical strategies can be used to kill bacteria.•Multifunctional chemical and physical strategies are required to reduce bacterial attachment and biofilm formation